Examination of the mode of action of the Almiramide family of natural products against the kinetoplastid parasite Trypanosoma brucei - Sanchez, Laura M.; Knudsen, Giselle M.; Helbig, Claudia; De Muylder, Geraldine; Mascuch, Samantha M.; Mackey, Zachary B.; Gerwick, Lena; Clayton, Christine; McKerrow, James H.; Linington, Roger G. (Journal of natural products, 2013)
Almiramide C is a marine natural product with low micromolar activity against Leishmania donovani, the causative agent of leishmaniasis. We have now shown that almiramide C is also active against the related parasite Trypanosoma brucei, the causative agent of human African trypanosomiasis. A series of activity-based probes have been synthesized to explore both the molecular target of this compound series in T. brucei lysates and site localization through epifluorescence microscopy. These target identification studies indicate that the almiramides likely perturb glycosomal function through disruption of membrane assembly machinery. Glycosomes, which are organelles specific to kinetoplastid parasites, house the first seven steps of glycolysis and have been shown to be essential for parasite survival in the bloodstream stage. There are currently no reported small-molecule disruptors of glycosome function, making the almiramides unique molecular probes for this understudied parasite-specific organelle. Additionally, examination of toxicity in an in vivo zebrafish model has shown that these compounds have little effect on organism development, even at high concentrations, and has uncovered a potential side effect through localization of fluorescent derivatives to zebrafish neuromast cells. Combined, these results further our understanding of the potential value of this lead series as development candidates against T. brucei.